1913 : In Search of the World Before the Great War - Emmerson, Charles (New York PublicAffairs, 2013)
"Today, 1913 is inevitably viewed through the lens of 1914: as the last year before a war that would shatter the global economic order and tear Europe apart, undermining its global pre-eminence. Our perspective narrowed by hindsight, the world of that year is reduced to its most frivolous features... In this illuminating history, Charles Emmerson liberates the world of 1913 from this "prelude to war" narrative, and explores it as it was, in all its richness and complexity. Traveling from Europe's capitals, then at the height of their global reach, to the emerging metropolises of Canada and the United States, the imperial cities of Asia and Africa, and the boomtowns of Australia and South America, he provides a panoramic view of a world crackling with possibilities, its future still undecided, its outlook still open."--Publisher's information.
Include Index and Illustration
Keywords: Nineteen thirteen, A.D -- History, Modern